The Chinese Teachings of Self-Cultivation to Form a Moral Being - Wen Ma; Yaqin Zhu; Chunli Li; Bo Zhang; Xin Tian (Recent Trends in Arts and Social Studies Vol. 8, 2023)
In ancient days, the Confucian classics tell us to pay close attention to rectify our thoughts and deeds. Nowadays, people who are concerned about the harmony of a society emphasize on the significance of self-cultivation. This article introduces the examples of the Chinese teachings of self-cultivation: to protect the weak ones; to cherish creatures; and to abstain from losing one’s trustworthiness, obloquy, and scolding and cursing. It argues that what is common among all the above mentioned representations in the nature of morality is benevolence, trustworthiness and ritual propriety – the contents of self-cultivation.